Determining the suitability of the outdoor environment for the elderly in Badahu Park, Qingdao, China / Jing Lu, Alamah Misni - Jing Lu; Misni, Alamah (UiTM Press, 2023)
A residential outdoor environment is crucial for the elderly. With the growth of the elderly population in China, more and more old residential outdoor environment needs to be more suitable for the elderly. The Seniors Outdoor Survey (SOS) tool was developed as an effective and reliable assessment tool to determine the needs and preferences of seniors in outdoor Spaces. This study used SOS tools to assess the environment outside the Bahu Lake Park residential area in Qingdao, Shandong Province, China. The outdoor environment is divided into two sections for five assessment domains. The final mean score of the whole environment was 85.85, the percentage compared with the total score was 88.37%, the interrater ICC of the trainer was 0.879, and the T-test value was 0.903. All five areas scored above 84%, indicating that Badahu Park is an age-friendly and safe outdoor space. The scoring of each project by the SOS tool can quickly identify existing problems and point the way for future construction. The results of this study can help project managers and designers determine the essential outdoor features for future construction and maintenance priorities.